Pengaruh Upah Minimum Provinsi, Tingkat Kemiskinan, dan Tingkat Pengangguran terhadap IPM di Indonesia - Tria Resmana, Rifky; Gunawan, Romi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of the Provincial Minimum Wage (UMP), Poverty Rate (TK), and Unemployment Rate (TPT) on the Human Development Index (HDI) in five provinces of Indonesia categorized as having moderate HDI from 2014 to 2023. The research employs a panel data regression method using the Fixed Effect Model (FEM) approach to capture variations across regions and time.The findings reveal that the UMP has a positive and significant impact on HDI, indicating that higher minimum wages contribute to improvements in human development. In contrast, the TPT negatively and significantly affects HDI, suggesting that higher unemployment rates hinder human development progress. Meanwhile, the TK variable shows no significant effect on HDI, implying that changes in poverty rates during the study period did not directly influence human development levels in these provinces.Furthermore, the results of the regression analysis show that UMP, TK, and TPT simultaneously have a significant impact on HDI, with an overall contribution of 98.65%. The remaining 1.35% is attributed to other factors not included in the research model.These results highlight the importance of policies aimed at increasing minimum wages and reducing unemployment to enhance community welfare and accelerate human development in provinces with moderate HDI. Policymakers are encouraged to design comprehensive strategies that prioritize employment creation and wage improvements as key levers for boosting human development outcomes across regions.